Origins of Multidecadal SST Variations in the Southern Atlantic and Indian Oceans Since the 1960s - Xing Gao; Yuanlong Li; Pengfei Lin; Lei Zhang; Qiuping Ren; Ying Lu; Fan Wang (Geophysical Research Letters, 2023)
Abstract Multidecadal sea surface temperature covariance in the southern Atlantic and Indian Oceans within the 20°–45°S band (termed the SAIOs) has been detected, but the origins of these variations remain uncertain. This study focuses on the decade‐long warming surge (0.43°C/decade) during 1965–1975 and the stalled warming pace (0.05°C/decade) thereafter. Observations and models overall suggest the essence of external forcing in controlling the warming rates of these two periods. Specifically, the 1963 eruption of Mount Agung caused an abrupt cooling of the SAIO, and the recovery of radiative heating during the following decade led to rapid surface warming. The persistent positive trend of the Southern Annular Mode since the late‐1970s has retarded the SAIO warming, primarily by enhancing surface wind speed and latent heat release. Although internal variability can also affect the SAIO through atmospheric teleconnections, its role is overall secondary during the two periods.